Selective and Sensitive Fluorescence Aptamer Biosensors of Adenosine Triphosphate - Chao Meng; Zhao Dai; Wenjuan Guo; Yuanyuan Chu; Guangping Chen (Nanomaterials and Nanotechnology)
A fluorescence resonance energy transfer (FRET)- based aptamer biosensor (aptasensor) for sensitive determination of adenosine triphosphate (ATP) was developed. The energy donor and acceptor were 5′-carboxyfluorescein (5′- FAM) and gold nanoparticles (AuNPs), respectively. AuNPs were linked to 3′-SH-DNA by Au-S bond. This aptasensor was obtained by the hybridization between the complementary DNA strands of the 5′-FAM and AuNPs. The detecting results indicated that the FRET increase efficiency (Fr) of detecting system at 519 nm was linear when the concentration of ATP target was about 0.1–10 mmol/L. Moreover, the aptasensors showed a good stability in different buffer conditions and a low- detection limit (15.2 nmol/L) for ATP.